Simultaneous Determination of Five Components of Chaihu-Shugan-San in Beagle Plasma by HPLC-MS/MS and Its Application to a Pharmacokinetic Study after a Single Dose of Chaihu-Shugan-San - Yong-liang Zhu; Hui-jun Wang; Hao Xue; Yi Zhang; Qian-shi Cheng; Ling-yun Chen; Xiang-jun Qiu (Journal of Analytical Methods in Chemistry)
Chaihu-shugan-san (CHSGS) has been widely used in China to treat depression and gastrointestinal diseases for thousands of years, but little is known about its pharmacokinetic properties. The purpose of our study is to develop a reliable and sensitive high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) method to detect five components in beagle plasma and study their pharmacokinetic after oral administration of CHSGS in beagles. An Agilent C18 column (2.1 × 150 mm, 3.5 μm) was used to separate the analytes, and the column temperature was maintained at 40°C. A gradient elution procedure was used with solvent A (acetonitrile) and solvent B (0.1% formic acid, aqueous) as mobile phases. The elution procedure was 60% B—10% B (0–3 min) and 10% B—60% B (3.1–4 min). The flow rate was 0.3 mL/min, and the total measurement time was 4 min. Within the determined range, the standard calibration curves of the five analytes had a satisfactory linear relationship (r2 ≥ 0.9923). The recovery rate (n = 6) of the five analytes was between 85.42% and 90.85%, and the matrix effects (n = 6) were between 94.52% and 103.91%. These results show that the validated method could be successfully applied to study the pharmacokinetic in beagles after a single dose of CHSGS.